Perceptually Equivalent Judgments Made Visually and via Haptic Sensory-Substitution Devices. Issue 4 (2nd October 2018) - Favela, Luis H.; Riley, Michael A.; Shockley, Kevin; Chemero, Anthony
ABSTRACT: According to the ecological theory of perception–action, perception is primarily of affordances, which are directly perceivable opportunities for behavior. The current study evaluated participants' ability to use vision and haptic sensory-substitution devices to support perceptual judgments of affordances involving the task of passing through apertures. Sighted participants made perceptual judgments about whether they could walk through apertures of various widths and their level of confidence in each judgment, using unrestricted vision and, when blindfolded, using two haptic sensory-substitution instruments: a cane-like wooden rod and the Enactive Torch, a device that converts distance information into vibrotactile stimuli. The boundary between aperture widths that were judged as pass-through-able versus non-pass-through-able was statistically equivalent across sensory modalities. However, participants were not as confident in their judgments using the rod or Enactive Torch as they were using vision. Additionally, participants' judgments with the haptic instruments were significantly more accurate than with vision. The results underscore the need to assess sensory-substitution devices in the context of functional behaviors.